Synthesis, theoretical and photovoltaic investigation of two 1,10-phenanthroline-based D-π-A organic dyes for dye-sensitized solar cells - Ozsan, Buse; Aydogdu, Seyda; Hatipoglu, Arzu; Erden, Ibrahim (SPRINGER INT PUBL AG, 2026)
In this study, two metal-free organic dyes (B1 and B3) with a D-pi-A architecture were synthesized and investigated for dye-sensitized solar cell (DSSC) applications. The dyes featured triphenylamine as electron donor, an imidazole pi-bridge, and 1,10-phenanthroline as anchoring unit. Notably, B3 incorporated multiple anchoring units, enabling direct comparison with single-anchor B1. Structural characterization was conducted using FT-IR, NMR, mass spectrometry, UV-Vis, and electrochemical measurements. Density functional theory (DFT) calculations indicated that B3 has a smaller HOMO-LUMO gap and greater charge localization at the anchor, implying more efficient electron injection. Device testing confirmed B3's superior performance, as DSSCs with B3 reached 0.61% power conversion efficiency compared to 0.28% for B1, highlighting a clear benefit of the multi-anchor design. While overall efficiencies remain modest, these findings demonstrate the significance of anchor group configuration in 1,10-phenanthroline-based DSSC sensitizers.
Keywords: 1,10-phenanthroline; Dye sensitized solar cell; Photovoltaic applications; Organic dyes; ANCHORING GROUPS; OPTICAL-PROPERTIES; EFFICIENCY; CONVERSION; INDEX; Chemistry